Design and test of tray-seedling sorting transplanter - Feng, Qingchun; Zhao, Chunjiang; Jiang, Kai; Fan, Pengfei; Wang, Xiu (International Journal of Agricultural and Biological Engineering, 2015)
In order to improve the automatic sorting and transplanting of tray-seedling and reduce labors strength, a new sorting transplanter was designed. According to the feature of normal seedling tray and manual grading method, the mechanical sorting procedure was defined. The key parts of sorting transplanter are as follows: an efficient transfer mechanism with aerodynamic buffer, a seedling identifying and measuring unit based on linear-structured vision, the extendible multi-grasper with wireless technology and the system controller. The experiments were conducted and showed that the transplanting success rate was 90.0% on the tray of 6×12 holes under the speed of 700 cycles per hour. The vision unit’s failed identifying rate for the superior pepper seedlings on five different trays was less than 10%, and the measurement error of seedling height was about 5 mm. Keywords: transplanter, tray seedling sorting, grasper, machine vision, wireless technology DOI: 10.3965/j.ijabe.20150802.1459